ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN PADA PT. BANK SUMUT - Wahid Siregar, Putra; Reza Septriawan, Muhammad; Nurhayati, Nurhayati (Jurnal Manajemen Akuntansi dan Ilmu Ekonomi, 2025)
This study aims to analyse the financial performance of PT Bank Sumut during the 2021-2023 period using the CAMEL method (Capital, Asset Quality, Management, Earnings, Liquidity), which is an important tool in assessing bank health. The banking sector in Indonesia has a crucial role in the national economy, so evaluating the financial performance of banks is very important to ensure operational sustainability and positive contributions to the economy. The data shows positive growth in assets and net profit, with total assets increasing from IDR38.01 trillion in 2021 to IDR40.62 trillion in 2022, and reaching IDR44.39 trillion in 2023. Net profit also increased from IDR613.50 billion in 2021 to IDR700.72 billion in 2022, and reached IDR740.08 billion in 2023. Despite these positive trends, an in-depth analysis is needed to identify the strengths and weaknesses of PT Bank Sumut, especially in the face of challenges caused by the COVID-19 pandemic and changing economic conditions. The results of the study are expected to provide valuable insights for management in formulating improvement strategies, for regulators to ensure compliance with applicable regulations, as well as for investors and the public interested in understanding the bank's financial performance.